2008
DOI: 10.1159/000167419
|View full text |Cite
|
Sign up to set email alerts
|

Selective Isolation of <i>Pseudallescheria</i> and <i>Scedosporium </i>Species from Respiratory Tract Specimens of Cystic Fibrosis Patients

Abstract: Background: Fungi of the Pseudallescheria/Scedosporium complex are known to be colonizers and infectious agents of the respiratory tract of cystic fibrosis (CF) patients. Colonized CF patients are at high risk for the development of disseminated scedosporiosis after lung transplantation. The detection of these fungi may be difficult, because they grow slowly and so will be overgrown by faster-developing microorganisms on the media routinely used in diagnostic laboratories. Objectives: To examine the usefulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 40 publications
3
37
0
1
Order By: Relevance
“…However, these fungi have gained attention during the past 2 decades mainly because of their recognition as common agents of colonization of the airways in patients with cystic fibrosis (CF). When appropriate culture media are used, the S. apiospermum species complex ranks second among the filamentous fungi recovered from respiratory specimens, with a prevalence ranging from 4.5 to 11.6% in patients (8)(9)(10)(11)(12). Although usually asymptomatic, this fungal colonization of the airways may sometimes lead to allergic bronchopulmonary mycoses, sensitization, or respiratory infections (8,13).…”
mentioning
confidence: 99%
“…However, these fungi have gained attention during the past 2 decades mainly because of their recognition as common agents of colonization of the airways in patients with cystic fibrosis (CF). When appropriate culture media are used, the S. apiospermum species complex ranks second among the filamentous fungi recovered from respiratory specimens, with a prevalence ranging from 4.5 to 11.6% in patients (8)(9)(10)(11)(12). Although usually asymptomatic, this fungal colonization of the airways may sometimes lead to allergic bronchopulmonary mycoses, sensitization, or respiratory infections (8,13).…”
mentioning
confidence: 99%
“…Rutin olarak kullanı-lan mikolojik besiyerlerinde Aspergillus ve Candida türlerinin üremesi sonucunda S.apiospermum varlığı gözden kaçmaktadır. Farklı immünsüpresif hasta gruplarında serolojik ve moleküler yöntemlerle alınan sonuçlar, bu mantarın, kültürle alınan sonuçlardan daha yüksek oranda bulunabileceğini göstermektedir 2,3 . Bu durum skedosporyozun gözden kaçan bir enfeksiyon olduğunu düşündürmektedir.…”
Section: Introductionunclassified
“…Some fungi, such as Scediosporim and Pseudallescheria are difficult to identify with these methods (Horré et al, 2009;Williamson et al, 2001). In those cases, molecular analysis using fungal ribosomal rRNA genes and the associated internal spacer regions (ITS) are employed (Bouchara et al, 2009;Hinrikson et al, 2005;Kumeda & Asao, 1996;Schmidt & Rath, 2003;Williamson et al, 2001;Zeng et al, 2007b).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Species-specific PCR and culturing have identified a few fungi, such as Aspergillus and Candida (Bakare et al, 2003;Cimon et al, 2001;Mearns et al, 1967). There have been reports of Scedosporium apiospermum, Exophilia sp., and Wangiella dermatitidis being cultured from CF sputa (Defontaine et al, 2002;Dixon & Polak-Wyss, 1991;Hennequin et al, 1997;Horré et al, 2004;Horré et al, 2009;Rogers et al, 2003;Williamson et al, 2001). Recent statistics have shown that there is an increase in the prevalence of fungi being detected in the CF patient which may be a consequence of aggressive antibacterial therapy (Nagano et al, 2007).…”
Section: High Throughput 454 Sequencing Identifies Bacteria and Fungimentioning
confidence: 99%